PERAN EKSTRAKURIKULER BIMBINGAN MEMBACA AL-QUR’AN (BMQ) DALAM MENINGKATKAN MINAT BACA AL-QUR’AN SISWA DI MA SUNAN KALIJAGA PAKUNCEN PATIANROWO NGANJUK TAHUN AJARAN 2018/2019 - Muhammad Bahkrul Munir; Hilyah Ashoumi (Universitas KH. A. Wahab Hasbullah, 2019)
This study aims to determine the ability of Sunan Kalijaga Madrasah Aliyah (MA) students in their ability to read the Qur'an in the Madrasah Aliyah (MA) Sunan Kalijaga. where there are still students who are not fluent and lack of interest in reading the Qur'an. This research is a descriptive research with a qualitative approach. The data generated from this research are in the form of descriptive data obtained from data in the form of writing, words, and documents originating from respondents or sources studied. The results showed that, the interest in reading the Qur'an as well as the ability to read the Qur'an the students at MA Sunan Kalijaga were still lacking. things that become a factor or cause are students who lack religious understanding and come from public schools.